2000 yılı ve sonrasında Türkiye’de meydana gelen ekonomik krizler ve uygulanan politikalar - Akçay, Berhu (My University, 2019)
2000’li yılları Türkiye ekonomisinin gidişatı bakımından incelediğimizde önceki yıllardan farkı enflasyonun düşüş seyrinde olması ve dezenflasyon kavramıdır. Çok yüksek oranlarda enflasyon oranlarını görmüş bir Türkiye ekonomisi son 10 yılda enflasyonu tek haneli rakamlara indirmeyi başarmıştır. Tek haneli enflasyon süreci süreklilik haline getirilebilirse ekonomiye faydası yüksek oranda olmaktadır. Enflasyon oranının düşük olması ekonomide belirsizliği azalttığı için yatırımlarında artmasına neden olmaktadır. Çünkü düşük faizler yatırımcıların kendilerini güvende hissetmelerine neden olmaktadır. Üretim ve istihdam artar, kişi başına düşen gelir artar, kalkınma ve büyüme olumlu etkilenir. Ekonominin istikrarlı ve güçlü olabilmesi için düşük enflasyon oranının korunması gerekmektedir.Türkiye ekonomisini 2000’li yıllardan sonra şekillendiren temel kavramlar küreselleşme ve dünya ekonomisine entegrasyon ve düşen enflasyondur. Bu durum Türkiye ekonomisini önemli fırsat olması ile birlikte riskleri de beraberinde getirmektedir.

The concept of disinflation and sustained low inflation rate are key differences for Turkish economy in terms of economic progress before 2000s and the previous years. Turkish economy which experienced the high rate of inflation managed to reduce the inflation into single-figure inflation rate within the last decade. Extended period of the single-figure inflation rate is very beneficial to the economy. Low inflation encourages to make more investments because it decreases the financial uncertainty. Low interest rate arising from the low inflation makes the investors feel more secure. Production, employment, per capita income, economic development and economic growth is affected positively under by these economic conditions including low interest rate and low inflation. Low inflation rate should be kept under control to make economy more strong and stable.The receded inflation, integration in the world economy and globalisation are basic concepts that shaped the Turkish economy after 2000s. Although it has some risks, this economic condition is also an economic opportunity for Turkish economy.
Keywords: Economic crisis; Economic Policies; Economics; Ekonomi; Ekonomik kriz; İktisadi Politikalar Crisis; Kriz; Turkey; Türkiye